TRANSAKSI KAS DAN BANK DENGAN SOFTWARE ACCURATE BAGI SMA KRISTOFORUS 1 - Verawati; Denny; Jeferry C (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Cash and banks are part of company assets that can be used in operational activities to earn profits. Good management of cash and banks can show the certainty of company's cash flow in the future. Therefore, accurate and precise accounting records are needed for every transaction related to cash and banks. The use of trusted accounting software is necessary to make it easier to record company transactions in order to produce reliable reports. Apart from that, the skills of human resources who operate accounting software also need to be trained and improved. The problem faced by Kristoforus 1 High School is that they want to provide accounting software skills related to cash and bank transactions to students who take accounting extracurriculars. The solution provided by the PKM team is to provide cash and bank transaction training using Accurate software. The training was carried out face-to-face at the computer room of Kristoforus 1 High School on 17 and 22 November 2023. The material presented included theory about cash and banks, then followed by cash and bank transactions that were directly inputted into Accurate software. The training activities went well, where students participated actively, understood the material provided, and were able to answer the quiz questions given correctly.